Recent Advances in the Synthesis of 5-Substituted 1H-Tetrazoles: A Complete Survey (2013–2018) - Mittal, Rupali; Awasthi, Satish K. (Synthesis, 2019)
Tetrazoles are synthetic organic heterocyclic compounds comprising of high nitrogen content among stable heterocycles. Tetrazoles, chiefly 5-substituted 1H-tetrazoles have been used as a bioisosteric replacement for carboxylic acids in medicinal chemistry. Various clinical drugs, including losartan, cefazolin, and alfentanil, contain the tetrazole moiety. There have been significant developments in the synthesis of 5-substituted 1H-tetrazoles. Researchers are still working to develop more efficient and ecofriendly methods for their synthesis. In this review, we provide a comprehensive discussion of the recent advancements in the field of synthesis of 5-substituted 1H-tetrazoles.1 Introduction2 The Role of 5-Substituted 1H-Tetrazoles in Medicinal Chemistry3 Synthesis of 5-Substituted 1H-Tetrazoles3.1 Microwave-Assisted Synthesis3.2 Heterogeneous Catalysts3.3 Nanoparticles as Heterogeneous Catalysts3.4 Miscellaneous Methods4 Sartans: A Class of Tetrazole-Based Commercial Drugs5 Conclusions
Keywords: tetrazole; [3+2] cycloaddition; heterogeneous catalysis; synthetic methods; medicinal chemistry